2013
DOI: 10.4103/0259-1162.123234
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous blood gas analysis: An alternative to arterial blood gas analysis for initial assessment and resuscitation in emergency and intensive care unit patients

Abstract: Arterial blood gas (ABG) analysis is the gold standard method for assessment of oxygenation and acid base analysis, yielding valuable information about a variety of disease process. This study is aimed to determine the extent of correlation between arterial and peripheral venous samples for blood gases and acid base status in critically ill and emergency department patients and to evaluate if venous sample may be a better alternative for initial assessment and resuscitation. The prospective study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
3
15
0
3
Order By: Relevance
“…Herrington WG et al, observed that potassium values of arterial samples were in agreement with the potassium values measured in serum [14]. Shilpi Awasthi, et al, observed that there was a strong correlation between the arterial sodium and potassium and venous sodium and potassium which were similar to the findings of the present study [15].…”
Section: Discussionsupporting
confidence: 90%
“…Herrington WG et al, observed that potassium values of arterial samples were in agreement with the potassium values measured in serum [14]. Shilpi Awasthi, et al, observed that there was a strong correlation between the arterial sodium and potassium and venous sodium and potassium which were similar to the findings of the present study [15].…”
Section: Discussionsupporting
confidence: 90%
“…1A). This is consistent with the findings of studies by Tregger et al, 3 Awasthi et al, 4 Middleton et al, 9 and Bo Ra kim et al, 10 which have shown a mean A-V difference for pH ranging from –0.04 to 0.053.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier studies have shown good correlation between ABG and VBG values with respect to pH, PCO 2 , and bicarbonate in adult patients presented to the emergency department and ICU. 3,4 Studies involving ICU patients have shown good correlation for potassium measured between ABG machine and point of care analyzers. 5,6 However, there is limited information regarding relationship between the venous and arterial values for pH, PCO 2 , bicarbonate, and electrolytes in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Awasthiet al, 8 conducted a prospective study to determine whether peripheral venous blood gas analysis can be an alternative to arterial blood gas analysis for initial assessment and resuscitation in emergency and intensive care unit patients. The study showed minimal mean difference and good correlation (r> 0.9) between arterial and peripheral venous sample for blood gases and acid base status but correlation in PO 2 measurement was poor (r< 0.3).…”
Section: Resultsmentioning
confidence: 99%